A Field survey of the sites of the commune of Mzir’a’s in the eastern zab in the wilaya of Biskra - aridj, nedjm eddine; hadji, yacine rabah (The Algerian Historical Journal, 2026)
The region of Numidia isconsidered one of the most important regions in the ancient period, as it was known for human settlement in it, which made it leave us important archaeological remains in many parts of it, including the ziban region. We carried out a comprehensive archaeological survey that defined a field of many archaeological sites in the ziban region, including the al-mzir’a area in the eastern zab, so that many sites that were mentioned by researchers but not studied, in addition to new archaeological discoveries represented in either sites or landmarks or artefacts.